Evaluasi Tatalaksana Awal Kejang Demam (Febrile Seizure) pada Anak di Rumah Sakit Haji Medan - Sabrina Budiarti; Nurcahaya Sinaga (UMSU, 2021)
Introduction: Febrile seizures are the most common seizure disorder occurring at 6 months to 60 months of age and do not have intracranial infections and metabolic disorders and a history of seizures due to epilepsy. Seizures cause anxiety for parents and sometimes take the wrong action. Anxiety for parents must be reduced so that the initial management of the seizure must be understood. Objective: Knowing the initial management carried out to treat febrile seizures in children at the Haji Hospital Medan. Methods: This study was retrospective with a cross sectional study design from medical records of children with febrile convulsions that met the inclusion criteria, namely patients with febrile seizures who were recorded in the medical records for the period January - December 2019. Results: There were 46 medical records of children with febrile seizure patients who Most were male (52.2%) and female (47.8%). The most common age group was 6 months - 2 years (71.7%). The most common diagnosis was Simple Fever Seizure (KDS) as much as 67.4%. And the duration of seizures was mostly found, namely 5 minutes (87.0%). There were 11 children who received anticonvulsant supp, 2 people were given anticonvulsant injection. Further management was given intermittent treatment, giving oral diazepam 9 people and maintenance treatment for 1 person. Conclusion: The initial management of febrile seizures was largely not given anticonvulsants because the seizures had stopped. Only 23.9% were given supp and intravenous anticonvulsants.